2017
DOI: 10.21315/mjms2017.24.4.13
|View full text |Cite
|
Sign up to set email alerts
|

Brown-Séquard Syndrome as a First Presentation of Multiple Sclerosis

Abstract: A female patient aged 48 years presented with sub-acute onset of weakness in right upper and lower limb over the past one month and numbness over left side of body below neck level. Multiple sclerosis (MS) presenting as Brown-Séquard syndrome is very rare. We present a case of hemicord myelitis which presented as Brown-Séquard syndrome as a first manifestation, which was later diagnosed as MS during subsequent relapses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Upon reviewing the literature, we found that MS is one of the rarest known causes of BSS with very few case reports in existence. 1 , 8 , 9 , 10 The exact incidence of BSS due to MS could not be found, likely secondary to its relative rarity. Occasionally, BSS presents as a complication in a patient with known MS, 11 but BSS as an initial presentation is even more rare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon reviewing the literature, we found that MS is one of the rarest known causes of BSS with very few case reports in existence. 1 , 8 , 9 , 10 The exact incidence of BSS due to MS could not be found, likely secondary to its relative rarity. Occasionally, BSS presents as a complication in a patient with known MS, 11 but BSS as an initial presentation is even more rare.…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by ipsilateral upper motor neuron motor weakness below the level of lesion, lower motor neuron type at the level of lesion, and loss of ipsilateral proprioception with contralateral loss of pain and temperature sensations below the level of lesion. 1 The syndrome was first described by Charles-Édouard Brown-Séquard in 1849 through his experiments with animal models. 2 Most commonly, BSS is caused by trauma such as stab wounds and is occasionally caused by tumors, with lesser known causes including degenerative diseases, infection, and ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…Short-segment myelitis (<3 vertebral segments) as the initial attack in multiple sclerosis is uncommon 4 . There are few case reports of Brown-Sequard syndrome as the initial manifestation of multiple sclerosis 5,6,7 . All cases were retrospectively analyzed, because multiple sclerosis diagnosis needs to be constructed with multiple clinical and imaging findings.…”
Section: Discussionmentioning
confidence: 99%